Preparation of Epon-embedded renal tissue for scanning electron microscopy - Wing-Ling, NG (1982)
A method for the preparation of Epon-embedded renal tissue for scanning electron microscopy (SEM) is described. This involves careful removal of Epon by potassium hydroxide in absolute methanol to expose the embedded kidney tissue. The method is simple and gives good surface morphology of the sectioned and trimmed surfaces of the tissue block. Both sectioned and intact glomeruli are well shown. The method also allows SEM observation of tubules and blood vessels.